"Breaking heart" due to hydrofluoric acid burns in a case of homicide. (December 2022) - Hu, Hsuan-Yun; Wei, Shyh-Yuh; Lin, Szu-Yu; Chen, Li-Hsuan; Pan, Chih-Hsin
Abstract: Homicide attacks in which hydrofluoric acid (HF) is used are very rare, and few studies have reported the pathological changes. Hypocalcemia is thought to be the cause of sudden death from HF; nevertheless, after neutralization of the blood concentration of calcium ions, HF-induced arrhythmia may still occur, suggesting that in addition to hypocalcemia, direct toxic effects of HF may play a pivotal role in myocardial damage. Here, we report a homicidal forensic autopsy case with pathological changes of the myocardium due to HF burns. Von Kossa staining and immunohistochemical staining were also performed. The cause of death was given as HF toxicity with direct toxic effects on myocardial damage as ischemic injury may occur prior to ventricular fibrillation in the present case. The present case shows that myocardial damage should be given more attention in the clinical treatment and forensic autopsy of HF burns. Highlights: Homicide attacks in which hydrofluoric acid is used are very rare but lethal. HF burns may cause severe myocardial damage either directly or indirectly. Contraction band necrosis and myofiber breakup are nonspecific but the only findings. Von Kossa staining may be indirect evidence of fluoride ions binding to calcium ions.